(3ceGd GdHdGZIs - (3bGHhS Hf hTecjQ Hf RjGQ Hf hQOGf TGg GdLjdj, CHh GdMSf, GdedbH TeS GdeYGdj,J (B403 (3g` s
(3ChdgG (B:s
(3bGd YHOGdQMef Hf Ydj GdjROGOj cfJ CfXQ ajeG Cdag bOGeI Hf LYaQ aj PcQ GdcJGHI hChQOg aj aUhd eSJNQLI s
(3BNQgG (B:s
(3hdG cajd ChbY HhaGbg ef NHjFI GdPjd hMeGd Gddjd, hdG hcjd CYR Ydjg ef GdefOjd hGdWHb s
(3QSGFdg LeYgG hSeGgG (B"(3ceGd GdHdGZI(B" (3YHOGdQMef Hf Ydj GdjROGOjs
(3hocJHJ YfhGfGJgG HGdMeQI hHHYV ChQGbgG WeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B170 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B91s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B153 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1509s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs